Mesoderm induction and patterning: Insights from neuromesodermal progenitors. (July 2022) - Martin, Benjamin L.
Abstract: The discovery of mesoderm inducing signals helped usher in the era of molecular developmental biology, and today the mechanisms of mesoderm induction and patterning are still intensely studied. Mesoderm induction begins during gastrulation, but recent evidence in vertebrates shows that this process continues after gastrulation in a group of posteriorly localized cells called neuromesodermal progenitors (NMPs). NMPs reside within the post-gastrulation embryonic structure called the tailbud, where they make a lineage decision between ectoderm (spinal cord) and mesoderm. The majority of NMP-derived mesoderm generates somites, but also contributes to lateral mesoderm fates such as endothelium. The discovery of NMPs provides a new paradigm in which to study vertebrate mesoderm induction. This review will discuss mechanisms of mesoderm induction within NMPs, and how they have informed our understanding of mesoderm induction more broadly within vertebrates as well as animal species outside of the vertebrate lineage. Special focus will be given to the signaling networks underlying NMP-derived mesoderm induction and patterning, as well as emerging work on the significance of partial epithelial-mesenchymal states in coordinating cell fate and morphogenesis.